Ground and satellite based detection of rangeland management in per humid grasslands of Argentina - Kurtz, Ditmar Bernardo (Faculty of Agriculture, Universität zu Bonn, 2020)
Tesis para obtener el grado de Master of Science, de la Rheinische Friedrich-Wilhelms-Universität zu Bonn, en enero de 2007